Similar and yet different - digitalisation and its consequences for individual occupational profiles : a comparison between industrial clerks and process mechanics - Conein, Stephanie [Verfasser]; Schad-Dankwart, Inga [Verfasser] (My University, 2019)
"This article uses two occupations as examples to show that while ongoing digitalisation often leads to similar changes at skilled worker level if consid-ered in general terms, closer investigation of the respective workplaces reveal that these changes exert different occupation-specific effects. Commonali-ties and differences in the occupations of industrial clerk and mechanic in plastics and rubber processing are highlighted with regard to technologies deployed, changed tasks and new skills requirements. The article concludes with some estimates of the further development of the two occupations giv-en the conditions of digitalisation." (Author's abstract ; BIBB-Doku)
Ähnlich und doch verschieden – Digitalisierung und die Folgen für einzelne Berufsprofile
Keywords: S 6.4.1.1 Warenkaufleute; S 6.2.1 Steinbearbeitung, Baustoffherstellung, Keramik, Glas, Chemie, Kunststoff, Papier, Druck; G 1.2.3.2 Anforderungen & Bedarfe; Industriekaufmann; Verfahrensmechaniker für Kunststoff- und Kautschuktechnik; Digitalisierung; Tätigkeitswandel; Berufswandel; Qualifikationsanforderung